Association of anesthesia and analgesia with long-term mortality after hip fracture surgery: an analysis of the Australian and New Zealand hip fracture registry - Lin, D-Yin; Woodman, Richard; Oberai, Tarandeep; Brown, Brigid; Morrison, Craig; Kroon, Hidde; Jaarsma, Ruurd (Regional anesthesia and pain medicine, 2023)
IntroductionHip fractures are a common frailty injury affecting a vulnerable geriatric population. It is debated if anesthetic and analgesic techniques are associated with altered risk for outcomes in hip fracture patients. This study aimed to determine the association of anesthesia and regional analgesia with all cause 12-month mortality and even longer-term mortality after hip fracture surgery in Australia and New Zealand.MethodsData from the Australian and New Zealand Hip Fracture Registry collected from 2016 to 2018, with a minimum follow-up of 12 months, were reviewed. Anesthesia type and use of regional nerve blocks were investigated. The primary outcome was all cause 12-month mortality.Results12-month mortality was 30.6% (n=5410) in a total of 17,635 patients. There was no difference in 12-month mortality between patients who received spinal or general anesthesia (p=0.238). The administration of a combination of general and spinal anesthesia for surgery to repair the fracture was an independent predictor of higher 12-month mortality (unadjusted complete case HR=1.17 (95% CI 1.04 to 1.31); p<0.001). Nerve blocks performed in both the emergency department (ED) and the operating theater (OT) were associated with reduced long-term mortality (median follow-up 21 months) with an unimputed unadjusted HR=0.86 (95% CI 0.77 to 0.96; p=0.043).ConclusionThere was no difference in the association of 12-month mortality between general and spinal anesthesia in patients undergoing hip fracture surgery. However, there was an association with a higher risk of 12-month mortality in patients who received both general and spinal anesthesia for the same surgery. Patients who received a regional nerve block in both the ED and the OT had a lower association of 12-month and longer-term mortality risk. The reasons for these findings remain unknown and should be the subject of further research investigation.